Custom fractional factorial designs to develop atorvastatin self-nanoemulsifying and nanosuspension delivery systems – enhancement of oral bioavailability - Hashem FM; Al-Sawahli MM; Nasr M; Ahmed OA (Dove Medical Press, 2015)
Fahima M Hashem,1 Majid M Al-Sawahli,2 Mohamed Nasr,1 Osama AA Ahmed3,4 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Helwan University, Cairo, Egypt; 2Holding Company for Biological Products and Vaccines (VACSERA), Giza, Egypt; 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Saudi Arabia; 4Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Minia University, Minia, Egypt Abstract: Poor water solubility of a drug is a major challenge in drug delivery research and a main cause for limited bioavailability and pharmacokinetic parameters. This work aims to utilize custom fractional factorial design to assess the development of self-nanoemulsifying drug delivery systems (SNEDDS) and solid nanosuspensions (NS) in order to enhance the oral delivery of atorvastatin (ATR). According to the design, 14 experimental runs of ATR SNEDDS were formulated utilizing the highly ATR solubilizing SNEDDS components: oleic acid, Tween 80, and propylene glycol. In addition, 12 runs of NS were formulated by the antisolvent precipitation–ultrasonication method. Optimized formulations of SNEDDS and solid NS, deduced from the design, were characterized. Optimized SNEDDS formula exhibited mean globule size of 73.5 nm, zeta potential magnitude of -24.1 mV, and 13.5 µs/cm of electrical conductivity. Optimized solid NS formula exhibited mean particle size of 260.3 nm, 7.4 mV of zeta potential, and 93.2% of yield percentage. Transmission electron microscopy showed SNEDDS droplets formula as discrete spheres. The solid NS morphology showed flaky nanoparticles with irregular shapes using scanning electron microscopy. The release behavior of the optimized SNEDDS formula showed 56.78% of cumulative ATR release after 10 minutes. Solid NS formula showed lower rate of release in the first 30 minutes. Bioavailability estimation in Wistar albino rats revealed an augmentation in ATR bioavailability, relative to ATR suspension and the commercial tablets, from optimized ATR SNEDDS and NS formulations by 193.81% and 155.31%, respectively. The findings of this work showed that the optimized nanocarriers enhance the oral delivery and pharmacokinetic profile of ATR. Keywords: nanostructures, optimization, experimental design, fractional factorial design